A mathematical model of interior ballistics for the amphibious rifle when firing underwater and its validation by measurement - Hung, Nguyen Van; Doan, Dao Van (Vietnam Journal of Science and Technology, 2020)
The paper is focused on the build of the interior ballistics model of amphibious rifle when firing underwater base on the standard interior ballistics of automatic rifle used gas operated principle. The presented mathematical model is validated and experimentally verified for the 5.56 mm underwater projectile fire on the 5.56 mm amphibious rifle. The result of this research can be applied to design the underwater ammunition, underwater rifle and amphibious rifle.